WORLD PRACTICE OF FINANCING INFRASTRUCTURE PROJECTS BASED ON PUBLIC-PRIVATE PARTNERSHIP - Miras Kuttybai,; Nazgul Davletbayeva,; Yerkenazym Orynbassarova,; Asel Kamenova, (Academic Journal of Physical and Chemical Sciences, 2019)
The article discusses the global practice of financing infrastructure projects based on public-private partnership with the determination of the possibility of application in Kazakhstan. It has been established that despite the presence of specific features of financing, support and the used schemes of interaction between the banking and real sectors of the economy through the use of the public-private partnership mechanism, they interact without fail with the participation of the state institution, whose goal is to support the interaction process using alternative tools such as guarantees, insurance, subsidies, tax breaks, etc. In the conditions of Russia and Kazakhstan, taking into account the Eurasian Economic Union, recommendations on the development of mechanisms for interaction between the banking and real sectors of the economy in the framework of the implementation of the infrastructure of publicprivate partnership have been proposed.